2017
DOI: 10.18632/oncotarget.15411
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatocellular carcinoma with portal vein tumor thrombus: advances and challenges

Abstract: Portal vein tumor thrombus is a frequent, challenging complication in hepatocellular carcinoma. Hepatocellular carcinoma patients with portal vein tumor thrombus may show worse liver function, less treatment tolerance and worse prognosis than patients without portal vein tumor thrombus, and they may be at higher risk of comorbidity related to portal hypertension. Western and some Asian guidelines stratify hepatocellular carcinoma with portal vein tumor thrombus together with metastatic hepatocellular carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 102 publications
0
45
0
1
Order By: Relevance
“…30 Conversely, in China, an increasing number of studies have suggested that surgical treatments were more beneficial than nonsurgical treatments. [31][32][33] Therefore, multicenter studies with a large sample size are needed for selecting treatment for patients with PVTT. If a prediction model for HCC prognosis could be developed, it will provide clinicians better treatment recommendations.…”
Section: B Amentioning
confidence: 99%
“…30 Conversely, in China, an increasing number of studies have suggested that surgical treatments were more beneficial than nonsurgical treatments. [31][32][33] Therefore, multicenter studies with a large sample size are needed for selecting treatment for patients with PVTT. If a prediction model for HCC prognosis could be developed, it will provide clinicians better treatment recommendations.…”
Section: B Amentioning
confidence: 99%
“…4 However, due to the insidious onset, rapid progress and low early diagnosis rate of liver cancer, most patients are already in the advanced stage of the disease at the time of diagnosis, and the treatment effect is not good. 5 In advanced liver cancer cases, the 5 years' tumor recurrence and metastasis rate are as high as 40~70%. 6 Therefore, to explore the molecular biology process underlying liver cancer progression will help us better understand this disease and find effective targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with HCC with relatively small tumor burden and tumor thrombus confined to the same hepatic lobe, resection to remove both the main tumor and the tumor thrombus in carefully selected patients is increasingly being performed, especially at highly specialized Asian centers, with reported median overall survival ranging from about 14 to 25 months. (93)(94)(95) In this patient with locally advanced HCC, defined as progressive disease despite LRT or portal vein invasion without extrahepatic disease, the decision on whether to transition from LRT to systemic therapy can be challenging. Two randomized, open-label phase 3 studies have compared Y-90 and sorafenib for locally advanced, unresectable Child-Pugh A/B7.…”
Section: Case 2 Part Cmentioning
confidence: 99%